Serie A, Nr. 19: für sozialdemokratische Wählerinitiative. (V.l.n.r.: Erhard, Barzel, Kiesinger, Strauss) - Staeck, Klaus (1974)
Serie A, Nr. 19: für sozialdemokratische Wählerinitiative. (V.l.n.r.: Erhard, Barzel, Kiesinger, Strauss).